Anticancer drugs in the aquatic ecosystem: Environmental occurrence, ecotoxicological effect and risk assessment. (August 2021) - Li, Dan; Chen, Hongxing; Liu, Hongsong; Schlenk, Daniel; Mu, Jingli; Lacorte, Silvia; Ying, Guang-Guo; Xie, Lingtian
Graphical abstract: Highlights: Order of acute toxicity: Platinum complexes > endocrine therapy agents > antibiotics. Crustaceans were most sensitive aquatic species to anticancer drugs. Most of anticancer drugs are persistent in the aquatic environment. Seven anticancer drugs should be priority concerned in the aquatic environment. Abstract: Anticancer drugs are a group of therapeutic agents used to enhance cell death in targeted cell types of neoplasia. Because of frequent use and eventual discharge, they have been often detected in wastewater from pharmaceutical factories and hospitals, domestic wastewater, and surface waters. The occurrence of these drugs in aquatic ecosystems and their effects on aquatic organisms have been poorly characterized. This review focuses on the global occurrence of major classes of anticancer drugs in water and sediments of freshwater ecosystems and their ecotoxicological effects at different biological levels. While the availability of data is fairly limited, concentrations of most anticancer drugs range from < 2 ng/L to 762 µg/L in receiving water, while levels in sediments and sludge vary from 0.25 to 42.5 µg/kg. Their detection frequencies were 58%, 52% (78%) and 59% in hospital wastewater, wastewater treatment plant effluents (influents) and surface water, respectively. Predicted log K ow values of vincristine, imatinib mesylate and tamoxifen are higher than 3 and have estimated half-lives>60 d in waters using quantitative structure–activity relationship models, indicating high potential for persistence and bioaccumulation. Based on a species sensitivity distribution evaluation of 9 compounds, crustaceans are most sensitive to anticancer drugs. The most hazardous compound is cisplatin which has a hazard concentration at the 5th percentile. For Daphnia magna, the acute toxicities of major classes of anticancer drugs are ranked as platinum complexes > endocrine therapy agents > antibiotics > antimetabolite agents > alkylating agents. Using hazard quotient analysis based primarily on the lowest observed effect concentrations (LOECs), cyclophosphamide, cisplatin, 5-fluorouracil, imatinib mesylate, bicalutamide, etoposide and paclitaxel have the highest hazard for aquatic organisms. Further research is needed to identify appropriate chronic endpoints for risk assessment thresholds as well as to better understand the mechanisms of action and the potential multigenerational toxicity, and trophic transfer in ecosystems.